Complete Excision of Nerve Originating Hemangioma: A Case Report - Mahmud, Nasir Uddin; Rahman Patwary, Md Shafiqur; Hasan, Mohammad Mainul; Tauhidur Rahman, Sarker Mohammad; Alam, Md Shariful (Eastern Medical College Journal, 2022)
The hemangioma is a hamartomatous malformation and not a true tumorous of the hemangioma occur during childhood. It affects three girls for every boy. Commonest site of involvement is skin. Nerve originating hemangioma refers when it arises from the vessels supplying the nerve (vasa nervosum). It is very rare condition and presents painful, soft, compressible swelling in the course of nerve. Microscopically, hemangioma consist of poorly demarcated, non-capsulated masses and leashes of vascular channels, most of which contain blood. Although diagnosis is clinical; FNAC, Doppler Ultrasonogram study, MRI and EMG all investigations are helpful for confirmation. Surgery is the main stay of treatment but recurrence may occur. Per-operative microsurgical facility and in recurrent cases, administration of corticosteroid can prevent recurrence. We have operated one case with our own circumstances and patient has got uneventful recovery in one year follow up. EMCJ. January 2022; 7(1): 32-35